Electromobility and Renewable Energy Sources: Comparison of Attitudes and Infrastructure in Poland and Germany - Mariusz Tomczyk; Henryk Wojtaszek; Małgorzata Chackiewicz; Małgorzata Orłowska (Energies, 2023)
In the face of global challenges related to climate change and sustainable development, comparing attitudes and infrastructure in the field of electromobility and renewable energy sources in different countries becomes crucial. The question of differences and similarities between Poland and Germany in these areas sheds light on the unique challenges and opportunities that the two countries present to each other. The aim of the study is to understand these dynamics, which can contribute to the shaping of more effective policies and strategies for green energy and sustainable mobility. This study was conducted through a review of Polish and foreign literature, the use of the method of tabular comparisons, and the analysis of a questionnaire that was used. These complex methods combined both quantitative and qualitative analysis, which allowed for an in-depth understanding and comparison of attitudes and infrastructure related to electromobility and renewable energy sources in Poland and Germany. The study revealed significant differences and similarities between Poland and Germany in terms of electromobility and renewable energy sources. Germany shows a higher level of urbanization, a higher share of electric car ownership, and better charging infrastructure, while in Poland there is a strong belief in the key role of renewable energy sources. These findings may have implications for future green energy initiatives and policies in both countries. The study presents a complex picture of electromobility and renewable energy sources in Poland and Germany, showing clear differences in awareness, infrastructure, and attitudes. Germany seems to be more advanced in these areas, while Poland shows a strong commitment to renewable energy sources. These conclusions do not exaggerate the differences, but underline the need for a case-by-case approach to green energy strategies in both countries.